Requirements of different trademarks promoting the local food productsto get to the market - Nagyné Pércsi, Kinga (Studia Mundi – Economica, 2018)
There is a wide range of supply from the local and regional product labels so the consumers can identify the products with local origin. According to the Eurobarometer Survey (2016) most of the citizens agreed in that the use of product label are very important, however the excess number of labels can cause distrust against the food quality schemes and so called “label fatigue”. There is a wide supply from applicable product labels also in Hungary in the case of local food. The aim of this article is to introduce the variety of the labelling schemes, to systemize the labels and trademarks which are applicable in case of local food. Finally it is also an aim to analyse the quality assurance functions of the labels on the basis of international and domestic publications. Exactly the variety of the applied labels and the consumers’ confusions relating to them put the development of an EU level local food labelling and quality scheme on the agenda because the basic functions of the labelling become this way endangered. These basic functions are that they can distinguish the product from the competing products, raise trust of the consumers. The EU regulation on the Agricultural Product Quality Scheme (2012) has already provisions relating to the opportunity to the development of a new common labelling scheme to promote local farming and marketing. I mentioned also the main requirements relating to this new forming scheme.